197k views
5 votes
What is (5y+6)-(2y-3)

User Nneka
by
6.0k points

2 Answers

4 votes

Hello there! :)

Answer:

3y+9

*The answer must have a positive sign.*

Explanation:

Distributive property: a(b+c)=ab+ac

First, you had to remove parenthesis.


5y+6-(2y-3)


=-2y+3


5y+6-2y+3

And then simplify and solve. You can also subtract by the numbers or add by the numbers.


5-2=3


6+3=9

Final Answer: →
3y+9

Hope this helps!

Thank you!

-Charlie

Have a great day!

:)

:D

User Nelsonwebs
by
5.5k points
4 votes

(5y + 6) - (2y - 3) = 5y + 6 - 2y - (-3)

= 5y + 6 - 2y + 3 combine like terms

= (5y - 2y) + (6 + 3) = 3y + 9

User Riyaz
by
4.9k points